Strategi Inventarisasi Aset Tetap oleh Pemerintah Desa Cileles dalam Meningkatkan Transparansi dan Akuntabilitas Pengelolaan Aset Desa - Deva Arista Guhaningtias; Elisa Susanti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This research aims to analyze the implementation of fixed asset inventory by the Village Government of Cileles, Jatinangor Subdistrict, Sumedang Regency, as part of an effort to establish transparent and accountable village asset governance. The main issue addressed in this research is the weakness in asset recording and reporting, particularly related to land, roads, networks, and irrigation assets that remain uncertified or lack recorded value in the Village Asset Inventory Card (Kartu Inventaris Barang/KIB). This study adopts a descriptive qualitative approach with data collected through in-depth interviews, field observations, and document analysis. The analytical framework refers to Kurniati’s (2017) four-stage inventory theory, which includes preparation, implementation, reporting, and follow-up stages. Findings indicate that although the inventory process follows formal procedures, it has not been optimally executed. Key challenges include limited asset legal documentation, lack of technical training for village operators, the absence of a structured follow-up system, and suboptimal use of the SIPADES application as a digital asset management tool. The study recommends strengthening human resource capacity, enhancing data system integration across platforms, and accelerating the asset certification process to support accurate, verifiable data as a foundation for effective village development planning.